Peran Modal Sosial Terhadap Livelihood Strategy Masyarakat Pengkalen Batu, Kecamatan Payung, Kabupaten Bangka Selatan - Isnawati Isnawati; Herdiyanti Herdiyanti; Bustami Rahman; Aimie Sulaiman; Laila Hayati; Amir Dedoe (Society, 2021)
This research is one of the studies that refer to the socio-economic conditions of the Bangka community, especially in Pengkalen Batu Hamlet, in carrying out livelihood strategies. This research aims to explain the livelihood strategies the people of Pengkalen Batu Hamlet implemented in carrying out their lives amid limited access away from the village, which makes the community have to survive. This is based on the variety of natural potentials owned by the community and can be utilized in carrying out life amidst the limitations possessed by the community. Conditions with limited access and far from rural and urban settlements encourage people to be more active and creative in managing nature wisely and wisely. The condition of assets the community owns varies from natural, physical, financial, social, and human capital. This research uses descriptive qualitative research methods and purposive sampling data collection techniques. Based on the results of the research, the Pengkalen Batu community carried out several livelihood strategies, including life engineering, job diversification strategies from the various natural potentials they had, then migration engineering strategies carried out by the local community. The three strategies carried out do not just appear. Still, a push for access to social capital makes people think and move creatively and innovatively in developing their natural potential.